Case report: Endovascular embolization of a cerebral pseudoaneurysm caused by SARS-CoV2 infection - García-Carmona, Juan Antonio; von Quednow, Enzo; Hernández-Fernández, Francisco; Molina-Nuevo, Juan David; García-García, Jorge; Palao, María; Segura, Tomás (Frontiers in Neurology, 2022)
Background: severe COVID-19 has been shown to produce convulsions, encephalitis, Guillain-Barré syndrome or cerebrovascular disease. However, only 4 case reports described subarachnoid or brain haemorrhage caused by ruptured cerebral aneurysms or pseudoaneurysms in patients with COVID-19. Cerebral pseudoaneurysms represent <1% of all intracranial aneurysms and have been related with radiation therapy, vasculitis, rupture of true saccular aneurysms, arteriovenous malformations and infections by bacteria and viruses, such as Epstein-Bar and Herpes virus. Case presentation: a 28-year-old Caucasian woman, with no medical history of interest and completely vaccinated against SARS-CoV-2, was admitted in Neurology due to progressive tetraparesis with areflexia, cough and fever of 38ºC. SARS-CoV2 PCR was positive while lumbar puncture, blood tests and electromyogram showed criteria for Guillain-Barré syndrome. Despite the treatment, the patient developed dyspnea and tetraplegia requiring invasive mechanical ventilation. Motor neurological improvement but decreased level of consciousness was observed on day 13th. Brain CT scan demonstrated an acute haematoma and cerebral arteriography showed a 4-mm pseudoaneurysm located in a branch of the left Middle Cerebral Artery. Given the high risk of rebleeding, endovascular treatment was decided. Therefore, complete embolization of the pseudoaneurysm was carried out by using the synthetic glue N-butyl-cyanocrylate. Two days later, the patient was clinical and neurological recovered and was discharged. Lastly, a new angiography showed no evidence of the pseudoaneurysm 3-weeks later. Conclusions: we report for first time, a patient suffering a severe immune reaction caused by SARS-CoV2 infection and developing a cerebral pseudoaneurysm treated with endovascular embolization without complications.